A comperative Study of Arch Widths Between Class I Crowded With Normal Occlusions (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2019)
Objectives: To test the hypothesis that there is no difference between adults with Class I crowded (CICR) and Class I normal (CIN) occlusions with respect to  width of the maxillary and mandibular arches and gender comparisons.Materials and Method: In this cross sectional study, 52 pairs of study models were selected from the patients and students of the Orthodontics and Dentofacial Orthopedics Department of Dhaka Dental Collage and Hospital and were divided into two groups, 27 pair of dental casts with normal occlusion, 25 pair of dental casts with Class I crowded malocclusion including equal males and female samples.Results: The result of this study evaluated two study groups (Normal occlusion and Class I crowded ). Between different arch dimension maxillary arch widths were found to have significantly smaller in Class I crowded malocclusion compared with Normal Class I occlusion.Conclusion: In conclusion, the hypothesis was partially rejected by the finding of the study.Ban J Orthod & Dentofac Orthop, April 2017; Vol-7 (1-2), P.1-5